Factors Contributing to the Stability of the Farmer Producer Organisations: A Study in West Bengal - Gorai, Sudip Kumar; Wason, Monika; Padaria, R. N.; Rao, D. U. M.; Paul, Ranjit Kumar (Indian Journal of Extension Education, 2022)
The study was conducted to assess the stability of Farmer Producer Organizations (FPOs) and the factors contributing to the stability of FPOs in West Bengal during 2020. Using random sampling procedure, data were collected from 120 farmer members from ten FPOs from four districts of the state namely Birbhum, Murshidabad, Purba Bardhaman and Nadia through personal interview method. For measuring the stability of FPOs, stability index was developed taking mutual trust, role clarity of the members, level of involvement of members in group works, satisfaction of the members, sense of attachment and conviction and sense of ownership as the indicators. The significant difference between the mean scores of stability index of high and low performing FPOs were observed with respect to the dimensions like satisfaction of the members, mutual trust, role clarity and sense of attachment and conviction. Attitude of members towards their FPO and cooperation were found to be significant contributor in developing better group stability within a high performing FPO. Attitude towards FPO, assimilation and competition were found to be the reliable predictors for the variance in group stability in low performing FPOs.
Keywords: Farmer producer organizations; Stability; Factors; West Bengal; Indicators